2016
DOI: 10.1111/cid.12308
|View full text |Cite
|
Sign up to set email alerts
|

Reosseointegration Following Regenerative Therapy of Tissue‐Engineered Bone in a Canine Model of Experimental Peri‐Implantitis

Abstract: These data demonstrated that tissue engineered bone of ASCs, BMP-2 gene delivery, and β-TCP could exert powerful therapeutic effect on peri-implantitis as expected, which may suggest a feasible way to maintain the stability and masticatory function of dental implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 36 publications
(80 reference statements)
3
52
0
Order By: Relevance
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the test group, in addition to a hydroxyapatite carrier and rhBMP‐2 also included periodontal ligament stem cells, compared to the carrier control. Finally, also in Beagle dogs the combination of β‐TCP as a carrier plus rhBMP‐2 and adipose tissue derived stem cells, compared with several controls reported a histological bone gain of 2.81 mm in the test group versus 1.31 mm in the control group (Xu et al, ). In all these studies the addition of rhBMP‐2 demonstrated a significant added value when compared with the controls.…”
Section: Discussionmentioning
confidence: 98%
“…The ligature‐induced peri‐implantitis experimental model used for this study has been extensively used to study the pathophysiology of peri‐implant diseases and the efficacy of different therapeutic interventions (Albouy, Abrahamsson, & Berglundh, ; Albouy, Abrahamsson, Persson, & Berglundh, ; Berglundh, Gotfredsen, Zitzmann, Lang, & Lindhe, ; Berglundh, Lindhe, Marinello, Ericsson, & Liljenberg, ; Lindhe et al, ; Marinello et al, ; Martins, Ramos, Baptista, & Dard, ; Xu et al, ; Zitzmann, Berglundh, Ericsson, & Lindhe, ). The application of submarginal ligatures enhanced plaque accumulation and the development of peri‐implantitis, evidenced by bone loss and the development of peri‐implant bone defects, mainly circumferential (Carral et al, ; Schwarz et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peri-implantitis is an inflammation occurring in osseous tissue surrounding the dental implant and can develop as a chronic progressive marginal inflammation, which can cause loss of bone tissue and function around the implant [1]. There are similarities in aspects of microbiology and clinical and pathological manifestations between peri-implantitis and periodontitis, but there are still differences in the rate and extent of inflammation, as well as in cell composition [2,3].…”
Section: Introductionmentioning
confidence: 99%